2010
DOI: 10.1093/mp/ssp100
|View full text |Cite
|
Sign up to set email alerts
|

PLEIOTROPIC REGULATORY LOCUS 1 (PRL1) Integrates the Regulation of Sugar Responses with Isoprenoid Metabolism in Arabidopsis

Abstract: The biosynthesis of isoprenoids in plant cells occurs from precursors produced in the cytosol by the mevalonate (MVA) pathway and in the plastid by the methylerythritol 4-phosphate (MEP) pathway, but little is known about the mechanisms coordinating both pathways. Evidence of the importance of sugar signaling for such coordination in Arabidopsis thaliana is provided here by the characterization of a mutant showing an increased accumulation of MEP-derived isoprenoid products (chlorophylls and carotenoids) witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Interestingly, expression of PRL1 is significantly repressed in the pgn mutant, suggesting that these two may have functional interaction in RNA metabolism in response to different abiotic and biotic stresses. In addition, prl1 plants are resistant to the methylerythritol phosphate pathway inhibitor clomazone, a phenotype observed with loss of function of LOI1, which encodes a mitochondrial PPRP (Kobayashi et al, 2007;Flores-Pérez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, expression of PRL1 is significantly repressed in the pgn mutant, suggesting that these two may have functional interaction in RNA metabolism in response to different abiotic and biotic stresses. In addition, prl1 plants are resistant to the methylerythritol phosphate pathway inhibitor clomazone, a phenotype observed with loss of function of LOI1, which encodes a mitochondrial PPRP (Kobayashi et al, 2007;Flores-Pérez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since PP2A is involved in abscisic acid and auxin signaling and PRL1 functions as a regulator of sugar, stress, and hormone response, it is possible that the HMGR activity is regulated by phytohormone and stress response. Furthermore, both MVA and MEP pathways have been shown to be coordinated by sugar and hormone molecules via the global regulator PRL1 (Flores-Perez et al, 2010).…”
Section: Regulations Of Ginsenosides Synthesismentioning
confidence: 99%
“…Whereas transcriptional modulation of HMGR has been demonstrated in many plant systems, evidence for mechanisms regulating HMGR activity at the posttranslational level is scarce. Thus, Nieto et al (2009) have shown that metabolic perturbations by enhancing or depleting the flux through the sterol pathway in Arabidopsis causes a compensatory response in HMGR activity, without changes in transcript or protein levels, and Flores-Pérez et al (2010) reported that the inactivation of the Arabidopsis WD protein PRL1 leads to reduced HMGR activity with no changes in transcript and protein levels. This effect could be related to the ability of PRL1 to interact and inhibit the activity of the Arabidopsis SNF1-related protein kinases (SnRK1) AKIN10 and AKIN11 (Bhalerao et al, 1999), presumably targeting them for ubiquitination and proteasomal degradation (Lee et al, 2008).…”
Section: Transcriptional Versus Translational Regulation Of Hmgrmentioning
confidence: 99%